Effect of Work Engagement, Work Environment and Work Spirit on Teacher Satisfaction - Nuning Nurna Dewi; Ach. Fathoni Rodli; Fitri Nurhidayati (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This study aims in general to prove and analyze the effect of work involvement, work environment and work morale on teacher job satisfaction at SDN Aeng Beje Kenek. The population of this study were all permanent teachers at SDN Aeng Beje Kenek IV, Kecamatan Bluto recorded in mid-2013 with a total of 80 people. the following results are obtained: (1) The three independent variables, namely work involvement, work environment and morale have a significant positive effect on teacher job satisfaction at SDN Aeng Beje Kenek IV Kecamatan Bluto, thus proving that the three independent variables simultaneously have a significant effect on teacher job satisfaction. (2) Involvement work has a positive effect on teacher job satisfaction. The regression coefficient of 0.3677 shows, if there is an increase in work involvement by 1 point, it will increase teacher job satisfaction by 0.3677 points. Although it has a positive significant effect, job involvement has the smallest effect on teacher job. (3) The work environment in this study has a positive and nutritious effect on teacher job satisfaction. (4) Morale is the most effective and greatest in increasing job satisfaction of a teacher.   Keywords: work involvement, work environment, Satisfaction